KETAHANAN SOSIAL MASYARAKAT DI PERBATASAN : STUDI KASUS DI PULAU SEBATIK - Ghafur, Muhammad Fakhry (Masyarakat Indonesia, 2018)
The border is a strategic area that has an important role to build and to defend a country’s sovereignty. Through this concept, the role of a border is very important, especially if it was associated with the improvement of a quality of society’s life in terms economic, social, political, cultural, environment, defense, and security. A border is an interaction area between globalization and locality which happens in daily life. The progress of a community life in border areas is expected to improve the social resilience in responding the most significant global pressure. Therefore, in order to build a border area, social resilience is needed as it is a very important aspect, especially in Sebatik Island. This paper reviews the potential of social resilience in border area, especially in Sebatik Island that is directly adjacent with Malaysia in both land and sea, by using the qualitative analysis approach and how to manage any potential in the border area to support economic, social, and political development for other areas.